High-intensity small-sided games versus repeated sprint training in junior soccer players - Eniseler, N.; Sahan, C.; Özcan, I.; Dinler, K. (Journal of Human Kinetics, 2017)
The aim of this study was to compare the effects of high-intensity small-sided games training (SSGT) versus repeated-sprint training (RST) on repeated-sprint ability (RSA), soccer specific endurance performance and short passing ability among junior soccer players. The junior soccer players were recruited from of a professional team (age 16.9 ± 1.1 years). The tests included the repeated-shuttle-sprint ability test (RSSAT), Yo-Yo Intermittent Recovery Test level 1 (Yo-Yo IR1) and Loughborough Soccer Passing Test (LSPT). Nineteen participants were randomly assigned to either the small-sided games training (SSGTG) (n = 10) or repeated-sprint training group (RSTG) (n = 9). Small-sided games or repeated-sprint training were added to the regular training sessions for two days of the regular practice week. The Wilcoxon signed-rank and Mann-Whitney U tests were used to examine differences in groups and training effects. A time x training group effect was found in the improvement of short-passing ability for the smallsided games training group which showed significantly better scores than the repeated-sprint training group (p = 0.05). Both groups showed similar improvements in RSAdecrement (p < 0.05). Only the repeated-sprint training group improved in the Yo-Yo IR1 (p < 0.05). This study clearly shows that high-intensity small-sided games training can be used as an effective training mode to enhance both repeated sprint ability and short-passing ability.